Applications of machine learning in big-data analytics and cloud computing - Pani, Subhendu Kumar 1980-; Tripathy, Somanath; Jandieri, George; Kundu, Sumit; Butt, Talal Ashraf (River Publishers, 2021)
Preface xv List of Contributors xxi List of Figures xxv List of Tables xxix List of Abbreviations xxxi 1 Pattern Analysis of COVID-19 Death and Recovery Cases Data of Countries Using Greedy Biclustering Algorithm 1 1.1 Introduction 2 1.2 Problem Description 3 1.2.1 Greedy Approach: Bicluster Size Maximization Based Fitness Function 4 1.2.2 Data Description 5 1.3 Proposed Work: COVID 19 Pattern Identification Using Greedy Biclustering 7 1.4 Results and Discussions 8 1.5 Conclusion 18 1.6 Acknowledgements 18 References 18 2 Artificial Fish Swarm Optimization Algorithm with Hill Climbing Based Clustering Technique for Throughput Maximization in Wireless Multimedia Sensor Network 23 2.1 Introduction 24 2.2 The Proposed AFSA-HC Technique 27 2.2.1 AFSA-HC Based Clustering Phase 28 2.2.2 Deflate-Based Data Aggregation Phase 33 2.2.3 Hybrid Data Transmission Phase 34 2.3 Performance Validation 34 2.4 Conclusion 40 References 40 3 Analysis of Machine Learning Techniques for Spam Detection
Keywords: Big data; Machine learning; Cloud computing; COMPUTERS / Database Management / Data Mining; SCIENCE / Energy